A synthesis method of cold incineration catalyst and catalyst prepared therefrom
By combining in-situ synthetic carbon materials with advanced catalytic oxidation materials, a cold incineration catalyst integrating adsorption enrichment and advanced oxidation functions was developed, which solved the problem of low VOCs purification efficiency at low temperatures in the existing technology, and achieved an efficient and suitable VOCs purification effect suitable for industrial production.
Patent Information
- Application Number
- CN202180099569.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-09-18
AI Technical Summary
The prior art has low purification efficiency of volatile organic compounds (VOCs), especially benzene, at low temperatures, and advanced oxidation technology has problems of low efficiency and limited application.
By combining in situ synthetic carbon materials with advanced catalytic oxidation materials, a cold incineration catalyst integrating adsorption enrichment and advanced oxidation functions was developed. The catalyst consists of a water-soluble titanium peroxide precursor, a MnO2-TiO2 composite precursor, a polyaniline-TiO2-MnO2 composite and a C-TiO2-MnO2 composite, and forms an activated carbon structure rich in oxygen-containing groups through the pyrolysis process.
It is effective to purify VOCs, especially benzene under mild reaction conditions, and the mesoporous structure of the catalyst is maintained intact, which is suitable for large-scale industrial production.
Smart Images

Figure CN117500588B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of industrial catalysts, and in particular relates to a synthesis method of a cold incineration catalyst integrating adsorption enrichment and advanced oxidation functions and a cold incineration catalyst prepared by the synthesis method. Background Art
[0002] According to the definition of the World Health Organization (WHO), Volatile Organic Compounds (VOCs) are the general term for volatile organic compounds with a melting point below room temperature and a boiling point between 50 and 260°C. VOCs have an important impact on the environment. On the one hand, they can form secondary aerosols through photochemical reactions, causing regional environmental problems such as haze; on the other hand, they are the most important form of pollution in the indoor environment. Taking formaldehyde and benzene as typical representatives of indoor air VOCs pollutants, they are extremely harmful to the human body. Formaldehyde is a carcinogen currently identified by the World Health Organization (WHO). Benzene, including benzene, toluene, ethylbenzene, xylene, etc., are toxic to the central nervous system and blood system of the human body. At present, the purification technology for VOCs can be simply divided into passive adsorption purification technology represented by activated carbon and active purification technology based on catalytic oxidation. Passive adsorption is the most widely used technology at present, with the characteristics of high efficiency, rapidity and diversity. However, it does not really play a role in degradation, but only transfers pollutants from one phase to another. After a certain amount of pollutants are adsorbed, it will become a pollution source to release the adsorbed pollutant gas for secondary pollution. Since there is no problem of adsorption saturation, catalytic oxidation technology does not need to frequently replace catalytic materials, has a long service life, less maintenance, and is easy to use. However, thermal catalytic oxidation technology represented by precious metal (such as Pt) catalytic system and manganese oxide (hopcalite catalyst), even though current research focuses on reducing the decomposition temperature of VOCs, for benzene series, there is no report of T90 temperature less than 100°C, and reaction temperature above 100°C is dangerous for application, which limits its application.
[0003] Advanced oxidation is a type of process that uses photoelectrochemical methods to produce highly active hydroxyl radicals that directly react with various organic compounds indiscriminately and degrade them into CO. 2 , H 2Low-temperature oxidation method of O. Considering that most catalytic reaction processes are surface reaction processes, for the purification process of low-concentration pollutants, especially trace pollutants, the mass transfer process usually becomes the rate-controlling step of the catalytic reaction. The corresponding catalytic oxidation process has also been criticized for its low efficiency and cannot be widely used. Therefore, the so-called "cold incineration", that is, to solve this problem, the adsorption-advanced oxidation catalytic system is widely used. For example, by combining a porous structure with an advanced oxidation catalyst to form a composite structure, the porous material can first enrich VOCs, and the advanced oxidant will produce reactive oxygen species (ROS) groups, such as OH· free radicals. After diffusing to the adsorbent, the high-energy OH· can directly oxidize the adsorbed VOCs to generate CO 2 With H 2 O. Through this ROS-mediated advanced oxidation process, the adsorption performance of the adsorbent material can be regenerated in situ, thus achieving a perfect combination of the rapid purification ability of the adsorbent material and the advantages of the catalytic oxidation material such as no secondary pollution. This achieves efficient low-temperature oxidation purification similar to the "incineration" of VOCs.
[0004] Activated carbon materials have developed pore structures, large specific surface areas and rich chemical groups, and are widely used VOCs adsorption and purification materials. Therefore, compounding activated carbon with catalysts to form adsorption-catalysis composite materials has received widespread attention. The impregnation method is a widely used process at present. Its principle is to load the active catalytic component solution on the surface of activated carbon by immersion, and then realize the catalyst synthesis method of firmly loading the active component and the base material through curing processes such as sintering. Although this type of method can obtain the expansion of the specific surface area of the catalyst, it sacrifices the adsorption capacity of the porous material. For environmental purification, especially low-concentration, high-air volume systems, rapid selective adsorption capacity is the key factor to ensure the purification rate. The present invention develops an adsorption-driven VOCs efficient purification nanostructure through an in-situ synthesized composite system of carbon materials and advanced catalytic oxidation materials, and realizes efficient purification of VOCs under mild reaction conditions. Summary of the invention
[0005] According to one aspect of the present invention, an object of the present invention is to provide a method for synthesizing an activated carbon-metal oxide composite cold incineration catalyst which is simple, easy to control, has good effects and is suitable for large-scale industrial production, the method comprising the following steps:
[0006] (1) Preparation of water-soluble titanium peroxide precursor
[0007] Dissolving a titanium hydroxide precursor with a hydrogen peroxide aqueous solution to obtain a metal titanium peroxide aqueous solution, wherein the molecular molar ratio of hydrogen peroxide to titanium ions in the titanium peroxide aqueous solution is 1:1 to 100:1;
[0008] (2) MnO 2 -TiO 2 Preparation of composite precursors
[0009] Add a certain amount of potassium permanganate to the titanium peroxide aqueous solution obtained in step (1) to control KMnO 4 The molar ratio of Ti to Ti is 0.01:1 to 10:1. After complete dissolution, heat and reflux at 90 to 100 °C for 0.5 to 4 hours to obtain TiO 2 -MnO 2 Complex with titanium peroxide;
[0010] (3) Polyaniline-TiO 2 -MnO 2 Preparation of complexes
[0011] Dissolve aniline monomer in an ethanol solution, wherein the volume concentration of the aniline monomer ethanol solution is 0.1% to 99.9%, and then add the TiO 2 -MnO 2 The composite of aniline and titanium peroxide, wherein the mass ratio of aniline monomer to Ti (calculated by added titanium hydroxide) in the final mixed solution is 0.1:1 to 20:1, and then reacting for 1 to 5 hours at 50 to 80°C and 100 to 300 rpm for stirring to obtain the final polyaniline-TiO 2 -MnO 2 Complex emulsion;
[0012] (4) C-TiO 2 -MnO 2 Preparation of complexes
[0013] The polyaniline-TiO 2 -MnO 2 The emulsion of the composite was centrifuged and precipitated, and the obtained precipitate was dried in an oven and then placed in a muffle furnace for programmed temperature calcination in an inert atmosphere: the temperature was programmed to 500°C at a rate of 5°C / min, and then kept constant for 2-6h to obtain C-TiO 2 -MnO 2 Cold combustion catalyst.
[0014] Preferably, the molecular molar ratio of hydrogen peroxide to titanium ion in step (1) is 1:1 to 80:1, more preferably 1:1 to 50:1.
[0015] Preferably, in step (1), KMnO 4 The molar ratio of Ti is 0.01:1 to 3:1, and more preferably 0.1:1 to 1:1.
[0016] Preferably, the volume concentration of the ethanol solution of aniline monomer in step (3) is 1% to 60%, more preferably 2% to 30%.
[0017] Preferably, the mass ratio of the aniline monomer to Ti (calculated as added titanium hydroxide) in step (3) is 0.2:1 to 15:1, more preferably 0.2:1 to 10:1.
[0018] Preferably, the inert atmosphere in step (4) is a nitrogen atmosphere or an argon atmosphere.
[0019] Preferably, the synthesis method according to the present invention is carried out as follows:
[0020] 100g of titanium hydroxide precipitate with a solid content of 4% was added with 100mL of a 30% aqueous hydrogen peroxide solution at room temperature and 200rpm stirring. The mixture was stirred until the precipitation was completely dissolved. Then, 5.2g of KMnO with a purity of 99% was added. 4 , heated to reflux at 100°C for 2h; then, at a stirring speed of 200rpm, 100mL of 30% aniline ethanol solution was added, and further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 6h, and then programmed to 500°C at a rate of 5°C / min in a muffle furnace in a nitrogen atmosphere, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black catalyst.
[0021] According to another aspect of the present invention, another object of the present invention is to provide a C-TiO 2 -MnO 2 A composite cold incineration catalyst, wherein the catalyst is prepared according to the synthesis method of the present invention.
[0022] According to another aspect of the present invention, another object of the present invention is to provide the C-TiO 2 -MnO 2 Use of composite cold incineration catalyst in catalytic degradation of VOCs.
[0023] Preferably, the C-TiO 2 -MnO 2 The composite cold incineration catalyst is used for catalytic degradation of VOCs, wherein the VOCs are aromatic VOCs, such as benzene, toluene, xylene, styrene, formaldehyde, benzaldehyde, etc., more preferably styrene.
[0024] Beneficial Effects
[0025] Compared with the preparation methods of similar catalysts in the prior art, the synthesis method of the present invention has simple process and mild reaction conditions. The mesoporous structure of the activated carbon generated in situ in the prepared composite catalyst remains intact, which is conducive to the adsorption of VOCs. 2 -MnO 2 It can effectively catalyze and decompose VOC. The synthesis method according to the present invention is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 The transmission electron microscope photograph shows the cold incineration catalyst product prepared in Example 1 of the present invention.
[0028] Figure 2 To show the XRD results of the cold incineration catalyst prepared in Example 1 of the present invention.
[0029] Figure 3 To show the IR results of the polymer product prepared in Example 1 of the present invention.
[0030] Figure 4 To show the specific surface area results of the cold incineration catalyst product prepared in Example 1 of the present invention.
[0031] Figure 5 To show the cold combustion catalytic results of the cold combustion catalyst product prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.
[0033] The key point of the present invention is to simultaneously initiate the KMnO 4The reduction of aniline and the polymerization of aniline monomers form PANi-MnO 2 -TiO 2 Composite structure precursor, and then pyrolysis to obtain C-MnO 2 -TiO 2 Structural cold incineration catalyst. Specifically, the technical points of the present invention are as follows:
[0034] 1) The free radicals formed by the peroxide bonds in titanium peroxide initiate the polymerization of aniline monomers to form an organic-inorganic composite nanostructure.
[0035] 2) Reduction of KMnO by the reductive property of the peroxide bond in titanium peroxide 4 Formation of MnO 2 Thus, MnO 2 -TiO 2 Advanced oxidation catalysts.
[0036] 3) Through the pyrolysis process and MnO 2 The activated carbon C-MnO rich in oxygen-containing groups was obtained by oxidation activation. 2 -TiO 2 Structural cold combustion catalyst.
[0037] In step (1) of the synthesis method according to the present invention, the molecular molar ratio of hydrogen peroxide to titanium ions is 1:1 to 100:1, preferably 1:1 to 80:1, and more preferably 1:1 to 50:1. In the synthesis method of the present invention, the amount of hydrogen peroxide added is very critical. Hydrogen peroxide not only complexes with titanium ions, but also acts as a KMnO 4 Reduction to form MnO 2 The hydrogen peroxide can be used as a reducing agent, and the free radicals formed by the peroxide bond can also act as an initiator for initiating the polymerization of the aniline monomer. Therefore, if the amount of hydrogen peroxide is too little, the above purpose cannot be achieved, but if the amount of hydrogen peroxide is excessive, for example, based on 1 mole of Ti ions, the number of moles of hydrogen peroxide is greater than 100, too many free radicals are formed in the subsequent steps, resulting in the inability to obtain the ideal aniline polymer, which in turn leads to the unsatisfactory mesopore size in the final product.
[0038] Preferably, in step (1), KMnO 4 The molar ratio of KMnO to Ti should be controlled to be 0.01:1 to 3:1, more preferably 0.1:1 to 1:1. 4 The molar ratio of KMnO to Ti is less than 0.01:1, that is, the amount of manganese added is insufficient, the doping effect is not obvious, and the catalytic effect is not ideal; if the KMnO 4 If the molar ratio of manganese to Ti is greater than 3:1, the presence of excess manganese will affect the TiO 2 The catalytic performance of the catalyst is poor, and the overall catalytic effect is not ideal.
[0039] According to step (3) of the synthesis method of the present invention, aniline monomer is added, and the polymerization of aniline monomer is initiated by free radicals formed by peroxide bonds. The amount of aniline monomer added has a significant effect on the mesoporous structure of the final composite catalyst. 2 and TiO 2 In the presence of the polymer, in-situ mixing is achieved during the subsequent calcination process. If too little aniline monomer is added, for example, the mass ratio of aniline monomer to Ti (calculated by added titanium hydroxide) in the final mixed solution is less than 0.1:1, it is difficult to generate carbon with a mesoporous structure, and the adsorption performance of VOC is greatly reduced; if it is greater than 20:1, the final generated carbon also does not have a good mesoporous structure, and at the same time, due to the large amount of generated carbon, MnO 2 and TiO 2 Preferably, the mass ratio of the aniline monomer to Ti (calculated as added titanium hydroxide) in step (3) is 0.2:1 to 15:1, more preferably 0.2:1 to 10:1.
[0040] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are commercially available products.
[0041] Example 1
[0042] 100g of titanium hydroxide precipitate with a solid content of 4% was added with 100mL of a 30% aqueous hydrogen peroxide solution at room temperature and 200rpm stirring. The mixture was stirred until the precipitation was completely dissolved. Then, 5.2g of KMnO with a purity of 99% was added. 4 , heated to reflux at 100°C for 2h; then, at a stirring speed of 200rpm, 100mL of 30% aniline ethanol solution was added, and further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 6h, and then programmed to 500°C at a rate of 5°C / min in a muffle furnace in a nitrogen atmosphere, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black cold combustion catalyst. The titanium hydroxide precipitate can be obtained by conventional methods, for example, by adding tetrabutyl titanate dropwise into deionized water under stirring.
[0043] The morphology of the obtained product is shown in Figure 1 Transmission electron microscope photos of the nanoscale composite material were obtained.
[0044] The obtained product crystal form, see Figure 2 The XRD results confirmed that the composite TiO 2 / MnO 2 Complex.
[0045] The infrared results of the obtained polymer product are shown in Figure 3 The FTIR results confirmed that the obtained C-TiO 2 -MnO 2 The black cold combustion catalyst contains polyaniline structure.
[0046] The specific surface area of the obtained product can be found in Figure 4 The BET results confirm that the obtained C-TiO 2 -MnO 2 The black cold combustion catalyst is a porous material.
[0047] Performance Testing
[0048] For the prepared cold incineration material, a penetration test was first conducted on styrene by using a fixed adsorption catalyst adsorption bed penetration column. 2g of the prepared cold incineration catalyst material was weighed and loaded into the penetration column. Pollutants with a specific concentration passed through the adsorption column, and the tail gas was absorbed by activated carbon. Before and after the gas passed through the adsorption column, the inlet and outlet concentrations were detected by a PID sensor. The adsorption saturated cold incineration catalyst material was placed at 200mW / cm 2 After irradiation with 185nm-254nm ultraviolet light for 4h, the adsorption capacity was tested again. The reaction conditions were: styrene concentration 50ppm, catalyst dosage 200mg, reaction temperature 25℃, reaction flow rate 200mL / min, space velocity 60000h -1 , 5% vol O 2 、N 2 To balance the gas, a gas chromatograph with a hydrogen ion flame detector was used to detect the concentration of styrene and carbon oxides. It was confirmed that it had an adsorption capacity of about 49 mg / g for styrene. At room temperature, the adsorption saturated cold incineration material was irradiated at a wavelength of 185nm to 254nm and an irradiation intensity of 200mW / cm 2 After irradiation with ultraviolet light for 4 h, the adsorption capacity of styrene was restored to 43 mg / g, confirming its adsorption photocatalytic oxidation ability (see Figure 5 ).
[0049] Example 2
[0050] 50g of titanium hydroxide precipitate with a solid content of 4% was stirred at 200rpm, and 100mL of a 30% aqueous hydrogen peroxide solution and 1.4g of KMnO with a purity of 99% were added.4 , heated to reflux at 100°C for 2h; then, at a stirring speed of 200rpm, 100mL of 20% aniline ethanol solution was added, and further reacted at a stirring speed of 500rpm for 5h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 6h, and the temperature was programmed to 500°C at a rate of 5°C / min, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black catalyst.
[0051] The performance test was carried out in a similar manner to that in Example 1. The prepared cold incineration material was first tested by a penetration test to confirm that it had an adsorption capacity of about 56 mg / g for styrene. The adsorption saturated cold incineration material was irradiated at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 h, the adsorption capacity recovered to 56 mg / g, confirming its adsorption photocatalytic oxidation ability.
[0052] Example 3
[0053] 100g titanium hydroxide precipitate with a solid content of 4% was stirred at 200rpm, and 100mL of a 30% aqueous hydrogen peroxide solution and 2.8g of KMnO with a purity of 99% were added. 4 , heated to reflux at 100°C for 2h; then, at a stirring speed of 200rpm, 100mL of 15% aniline ethanol solution was added, and further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 2h, and the temperature was programmed to 500°C at a rate of 5°C / min, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black catalyst.
[0054] The performance test was carried out in a similar manner to that in Example 1. The prepared cold incineration material was first tested by a penetration test to confirm that it had an adsorption capacity of about 32 mg / g for styrene. The adsorption saturated cold incineration material was irradiated at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 h, the adsorption capacity recovered to 32 mg / g, confirming its adsorption photocatalytic oxidation ability.
[0055] Example 4
[0056] 200g titanium hydroxide precipitate with a solid content of 4% was stirred at 200rpm, and 100mL of a 30% aqueous hydrogen peroxide solution and 1.1g of 99% pure KMnO4 , heated to reflux at 100°C for 2h; then, 100mL of 5% aniline ethanol solution was added at a stirring speed of 200rpm, and further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 2h, and the temperature was programmed to 500°C at a rate of 5°C / min, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black catalyst.
[0057] The performance test was carried out in a similar manner to that in Example 1. The prepared cold incineration material was first tested by a penetration test to confirm that it had an adsorption capacity of about 20 mg / g for styrene. The adsorption saturated cold incineration material was irradiated at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 h, the adsorption capacity recovered to 20 mg / g, confirming its adsorption photocatalytic oxidation ability.
[0058] Example 5
[0059] 200g titanium hydroxide precipitate with a solid content of 4% was stirred at 200rpm, and 100mL of a 30% aqueous hydrogen peroxide solution and 2.2g of KMnO with a purity of 99% were added. 4 , heated to reflux at 100°C for 2h; then, 100mL of 2% aniline ethanol solution was added at a stirring speed of 200rpm, and further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 2h, and the temperature was programmed to 500°C at a rate of 5°C / min, and then kept at a constant temperature for 4h to obtain C-TiO 2 -MnO 2 Black catalyst.
[0060] The performance test was carried out in a similar manner to that in Example 1. The prepared cold incineration material was first tested by a penetration test to confirm that it had an adsorption capacity of about 10 mg / g for styrene. The adsorption saturated cold incineration material was irradiated at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 h, the adsorption capacity recovered to 10 mg / g, confirming its adsorption photocatalytic oxidation ability.
[0061] Comparative Example 1
[0062] The composite catalyst was prepared in the same manner as in Example 1 except that 470 mL of a 30% by mass aqueous hydrogen peroxide solution was added, i.e., the molecular molar ratio of hydrogen peroxide to titanium ions was about 120:1. The composite catalyst had an adsorption capacity of about 1 mg / g for styrene.
[0063] Comparative Example 2
[0064] In addition to adding 16 g of 99% pure KMnO 4 In addition, the composite catalyst was prepared in the same manner as in Example 1, and its adsorption capacity for styrene was about 46 mg / g, but at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 hours, the residual adsorbed styrene was found to be 16 mg / g, which proved that there was residual styrene and the catalytic effect was not ideal.
[0065] Comparative Example 3
[0066] The composite catalyst was prepared in the same manner as in Example 1 except that 1 mL of 30% volume concentration aniline ethanol solution was added, i.e., the mass ratio of aniline monomer to Ti (calculated as titanium hydroxide) was less than 0.1:1. No mesoporous structure could be formed, and the composite catalyst had an adsorption capacity of about 2 mg / g for styrene.
[0067] Comparative Example 4
[0068] The composite catalyst was prepared in the same manner as in Example 1 except that 200 mL of 30% aniline ethanol solution was added, i.e., the mass ratio of aniline monomer to Ti (calculated as titanium hydroxide) was greater than 20:1. The mesoporous structure formed had an adsorption capacity of about 15 mg / g for styrene at a wavelength of 185 nm to 254 nm and an irradiation intensity of 200 mW / cm 2 After irradiation with ultraviolet light for 4 hours, the residual adsorbed styrene was found to be 4 mg / g, which proved that there was residual styrene and the catalytic effect was not ideal.
[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for synthesizing an activated carbon-metal oxide cold incineration catalyst, the method comprising the following steps: (1) Preparation of water-soluble titanium peroxide precursor Dissolving a titanium hydroxide precursor with a hydrogen peroxide aqueous solution to obtain a titanium peroxide aqueous solution, wherein the molecular molar ratio of hydrogen peroxide to titanium ions in the titanium peroxide aqueous solution is 1:1 to 100:1; (2) Preparation of MnO2-TiO2 composite precursor Add a certain amount of potassium permanganate to the titanium peroxide aqueous solution obtained in step (1), control the molar ratio of KMnO4 to Ti to be 0.01:1 to 10:1, and after complete dissolution, heat and reflux at 90 to 100° C. for 0.5 to 4 hours to obtain a complex of TiO2-MnO2 and titanium peroxide; (3) Preparation of polyaniline-TiO2-MnO2 composite Dissolve aniline monomer in an ethanol solution, wherein the volume concentration of the aniline monomer ethanol solution is 0.1% to 99.9%, then add the TiO2-MnO2 and titanium peroxide complex obtained in step (2), wherein the mass ratio of aniline monomer to Ti (calculated as titanium hydroxide added) in the final mixed solution is 0.1:1 to 20:1, and then react for 1 to 5 hours at 50 to 80° C. and 100 to 300 rpm stirring conditions to obtain a final polyaniline-TiO2-MnO2 complex emulsion; (4) Preparation of C-TiO2-MnO2 composite The emulsion containing the polyaniline-TiO2-MnO2 composite prepared in step (3) is centrifuged and precipitated, and the obtained precipitate is dried in an oven, and then placed in a muffle furnace for programmed temperature calcination in an inert atmosphere: the temperature is programmed to 500°C at a rate of 5°C / min, and then kept at a constant temperature for 2-6 hours to obtain a C-TiO2-MnO2 cold incineration catalyst.
2. The synthesis method according to claim 1, characterized in that The molecular molar ratio of hydrogen peroxide to titanium ion in step (1) is 1:1 to 80:
1.
3. The synthesis method according to claim 2, characterized in that The molecular molar ratio of hydrogen peroxide to titanium ion in step (1) is 1:1 to 50:
1.
4. The synthesis method according to claim 1, characterized in that The molar ratio of KMnO4 to Ti in step (1) is 0.01:1 to 3:
1.
5. The synthesis method according to claim 4, characterized in that The molar ratio of KMnO4 to Ti in step (1) is 0.1:1 to 1:
1.
6. The synthesis method according to claim 1, characterized in that The volume concentration of the ethanol solution of aniline monomer in step (3) is 1% to 60%.
7. The synthesis method according to claim 6, characterized in that The volume concentration of the ethanol solution of aniline monomer in step (3) is 2% to 30%.
8. The synthesis method according to claim 1, characterized in that The mass ratio of the aniline monomer to Ti (calculated as added titanium hydroxide) in step (3) is 0.2:1 to 15:
1.
9. The synthesis method according to claim 8, characterized in that The mass ratio of the aniline monomer to Ti (calculated as added titanium hydroxide) in step (3) is 0.2:1 to 10:
1.
10. The synthesis method according to claim 1, characterized in that The inert atmosphere in step (4) is a nitrogen atmosphere or an argon atmosphere.
11. The synthesis method according to claim 1, characterized in that: The synthesis method is carried out as follows: To 100g of titanium hydroxide precipitate with a solid content of 4%, 100mL of a 30% mass percent hydrogen peroxide solution was added at room temperature and under stirring at 200rpm, and stirring was continued until the precipitate was completely dissolved, then 5.2g of KMnO4 with a purity of 99% was added, and the mixture was heated to reflux at 100°C for 2h; then, 100mL of a 30% volume percent aniline ethanol solution was added at a stirring speed of 200rpm, and the mixture was further reacted at a stirring speed of 500rpm for 4h to obtain a brown emulsion; the prepared emulsion was centrifuged and precipitated, and the obtained precipitate was dried in an oven at 100°C for 6h, and then the temperature was programmed to 500°C at a rate of 5°C / min in a nitrogen atmosphere in a muffle furnace, and then kept at a constant temperature for 4h to obtain a C-TiO2-MnO2 black catalyst.
12. A C-TiO2-MnO2 composite cold incineration catalyst, which is prepared according to the synthesis method according to any one of claims 1 to 11.
13. Use of the C-TiO2-MnO2 composite cold incineration catalyst according to claim 12 in catalytic degradation of VOCs.
14. The use according to claim 13, characterized in that The VOCs are benzene, toluene, xylene, styrene, formaldehyde and benzaldehyde.
15. The use according to claim 14, characterized in that The VOCs is styrene.
Citation Information
Patent Citations
Vanadium manganese composite catalyst for removing nitrogen oxide in incineration gas and preparation method thereof
CN101972649A
Porous carbon loaded titanium dioxide composite manufactured by utilizing ionic liquid / polyaniline and method and application thereof
CN103349971A